THE TYPES AND FACTORS OF CODE SWITCHING IN “ENGLISH TIME” COURSE - Suhardianto Suhardianto; Afriana Afriana (Asosiasi dosen IDEBAHASA KEPRI, 2022)
In multilingual country, code switching is common in Indonesia. Code switching is the process of switching from one language into other language. Code switching also often appears in the English as foreign language (EFL) classroom. In learning English as EFL, the students in English course tend to switch their language. This research focuses on analyzing types of code switching and factors that cause the students to switch code by using sociolinguistic approach. The purpose of this study is to find out the types of code switching and factors that cause it in “English Time”. This research is a descriptive qualitative research in which the data are taken by observation method, specifically experimental observation, and involved conversation observation technique. The findings of the research reveal that there are three types of code switching occurred in “English Time”; tag-switching, intra-sentential switching, and inter-sentential switching. Moreover, there are eleven factors that cause the students to switch code; to emphasize a point, easy to convey a message, habitual experience, repetition to clarify a message, intimacy, affected with the addressee, to continue a pronouncement, easy to convey an idea, lack of vocabulary, to show different event, and to give explanation.